THE HEGEMONY OF HAMAS AND ITS IMPACT ON THE SOCIAL BEHAVIOR OF THE PALESTINIAN SOCIETY - Ahmad Jazuli; Suryo Ediyono; Abdul Malik; Alif Al Hilal Ahmad; Siti Muslifah (CMES (Center of Middle Eastern Studies), 2023)
This article explains the Hamas movement’s influence on Palestinian social conditions. This paper’s purpose is to describe the hegemony of Hamas in Palestine and its influence on the social behavior of the Palestinian people. The problem in this study is how the Hamas movement affects the social conditions of the Palestinian people. This research used a qualitative interpretive method and a hermeneutic method. This study uses Gramsci’s theory of hegemony as a scalpel. The results of this paper indicate that the hegemony of Hamas in Palestine affects the mindset, behavior, and vision of the Palestinian people. The Hamas movement influences people’s minds to defend and fight for the Palestinian territories from Israel. Hamas also forms the mindset of the people to seize power from Fatah, which is its political opponent in Palestine, who has different views on the form of a Palestinian state.